Media construction of the link between forest fires and climate change in the Spanish regional press - Erviti Ilundáin, María Carmen (Estudios sobre el Mensaje Periodístico, 2026)
Wildfires constitute one of the most significant environmental risks in the context of climate change. During the summer of 2025, Spain experienced one of the most severe wildfire outbreaks of recent decades, with a particularly significant impact in Galicia, Castile and León, and Extremadura. This study examines how the regional press in these territories constructed media narratives around this crisis, paying particular attention to the presence—or absence—of an explicit link between wildfires and climate change. The research is based on a quantitative and qualitative content analysis of 142 articles published in five leading regional and provincial newspapers. The analysis examines explicit references to climate change, dominant journalistic frames, and the actors who introduce climate-related references in media coverage, as well as the role of journalistic genres in constructing this connection. The results show that only a small minority of articles (4.7%) establish a direct relationship between wildfires and climate change, confirming the limited presence of this explanatory frame in the regional press. Political framing predominates, particularly in connection with the proposal of a State Pact on climate change, while climate explanations appear as secondary elements and rely mainly on statements from expert sources external to journalistic routines. Overall, the coverage reveals weak territorialization of climate risk and a clear disconnect between the magnitude of the event and the depth of media treatment, placing the Spanish case in line with international evidence on media coverage of large-scale wildfires.